-p(3p+5)=

Simple and best practice solution for -p(3p+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -p(3p+5)= equation:


Simplifying
-1p(3p + 5) = 0

Reorder the terms:
-1p(5 + 3p) = 0
(5 * -1p + 3p * -1p) = 0
(-5p + -3p2) = 0

Solving
-5p + -3p2 = 0

Solving for variable 'p'.

Factor out the Greatest Common Factor (GCF), '-1p'.
-1p(5 + 3p) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0

Subproblem 2

Set the factor '(5 + 3p)' equal to zero and attempt to solve: Simplifying 5 + 3p = 0 Solving 5 + 3p = 0 Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3p = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3p = 0 + -5 3p = 0 + -5 Combine like terms: 0 + -5 = -5 3p = -5 Divide each side by '3'. p = -1.666666667 Simplifying p = -1.666666667

Solution

p = {0, -1.666666667}

See similar equations:

| -1+2x=-4x+23x | | 6x(6x+3)=48 | | 8x=67 | | 32+20x= | | 10=5v-3v | | x^7y^9/y^2 | | 8x-4x+5=3 | | 420=12X*X | | -4(2f+11)=44 | | y^-9/y^-3 | | -8k(2-d)= | | 4-a=4 | | -108+11x=-x+132 | | 3r(-t-2)= | | 6h-25=35 | | 3.50+2.50+3t=26.50 | | 10x-3=4x+8 | | 3-3*2=0 | | -2f(t+2)= | | 10a-10=6a+2 | | 3(x+5y)+2x+y= | | -17+v=-17 | | 5(2u+3)= | | -13v=156 | | -3(3h+1)= | | 11x+3y=-5 | | 9a-30=78 | | a/30=3/10 | | 7(2a+1)= | | 15x-5y=45 | | x^2+225-289=0 | | 4s-5=-12+5s |

Equations solver categories